The Different Effect Of Wobble Board Exercise And Elastic Resistant Band Exercise On Stabilization Of The Ankle Joint In The Case Of Ankle Sprain - Sebianto, Odhe Laga; Kasimbara, Rachma Putri; Abdullah, Ahmad; Fau, Yohanes Deo (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: To identify that proprioceptive training using a wobble board is different from ankle muscle strengthening training using elastic resistance rubber in reducing foot and ankle disability in cases of chronic ankle sprains.Methods: This article is used an experimental method, to see the difference between wobble board exercise and ankle muscle strengthening training using elastic resistance rubber in reducing foot and ankle disability in cases of chronic ankle sprains. The first treatment group was wobble board exercise and Group II was ankle muscle strengthening training using elastic resistance rubber. FADI measurements were carried out before and after treatment with a pre-test and post-test group design.Results: exercises using Wobble Board and Elastic Resistant Band have differences, they can be used to reduce foot and ankle disability according to needs by taking into account age, tissue conditions, workload, and position at work. Conclusion: Proprioceptive training with a wooble board can reduce foot and ankle disability in cases of chronic ankle sprains with values before 25.90+ 15.56 and after treatment 6.60 + 5.03. Ankle muscle strengthening training with elastic resistance rubber can reduce foot and ankle disability in chronic ankle sprain cases with a value before treatment 44.90 + 18.80 after treatment 13.80 +10,30. Differences in proprioceptive training using a wooble board with ankle muscle strengthening training with elastic resistance rubber in reducing foot and ankle disability in cases of chronic ankle sprains with a difference of 19.30±12.57 in Group I and 31.10±12,19 in Group II.